2016
DOI: 10.1097/md.0000000000004696
|View full text |Cite
|
Sign up to set email alerts
|

A new multiparameter integrated MELD model for prognosis of HBV-related acute-on-chronic liver failure

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The current study developed a novel online individual mortality risk predictive tool based on an RSF algorithm [35,36] age, [35,37,38] INR, [4,36,38,39] RDW, [40,41] AKI, [42][43][44] and serum sodium level. [45,46] The RSF algorithm could identify the variables that had a nonlinear effect on prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study developed a novel online individual mortality risk predictive tool based on an RSF algorithm [35,36] age, [35,37,38] INR, [4,36,38,39] RDW, [40,41] AKI, [42][43][44] and serum sodium level. [45,46] The RSF algorithm could identify the variables that had a nonlinear effect on prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The variable importance assessment through the RSF algorithm further proved HE, age, serum sodium level, AKI, RDW, and INR as risk factors for ACLF patients. Previous studies have provided strong clinical evidence for the following variables as risk factors for ACLF patients: HE, [35,36] age, [35,37,38] INR, [4,36,38,39] RDW, [40,41] AKI, [42–44] and serum sodium level [45,46] …”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that patients with high AFP had greater regeneration activity and thus a better response to ALSS. Luo et al combined MELD with AFP, HE, WBC, and age to generate a new prognostic model to predict the prognosis of HBV‐ACLF patients. This model performed a higher AUROC than MELD, MELD‐Na, and iMELD.…”
Section: Discussionmentioning
confidence: 99%
“…The maternal outcomes were also good in all cases. Although our study could not assess these prognostic scores, some good-quality studies have been conducted on them [ 34 , 35 ]. Very few studies have investigated whether these scoring systems are applicable to pregnant women.…”
Section: Discussionmentioning
confidence: 99%